Management strategy based on the concept of Magnet Hospital to reduce the turnover rate among nurses ("磁性医院"管理理念在降低护士离职率中的应用) - SUN Hongyu (孙宏雨); ZHAO Zeying (赵泽英); ZHAO Yumeng (赵瑜萌); KE Xiuliu (柯秀柳) (Journal of International Translational Medicine Limited, 2021)
This paper summarized the application experience of management strategy based on the concept of Magnet Hospital to reduce the turnover rate among nurses. Management strategies can be divided into four areas including humanistic care, humanistic nursing management, quality improvement and development of the clinical nurse specialist, in order to stabilize the nursing team and reduce the turnover rate among nurses. (本文总结"磁性医院"管理理念在降低护士离职率中的应用经验, 通过有效落实人文关怀、人性化护理管理、护理质量管理、专科发展4个方面的措施, 有效提高了护理团队的稳定性, 降低了护士离职率。)